2018
DOI: 10.2147/ott.s145473
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker expression in rectal cancer tissue before and after neoadjuvant therapy

Abstract: PurposeIntraoperative identification of rectal cancer (RC) can be challenging, especially because of fibrosis after treatment with preoperative chemo- and radiotherapy (CRT). Tumor-targeted fluorescence imaging can enhance the contrast between tumor and normal tissue during surgery. Promising targets for RC imaging are carcinoembryonic antigen (CEA), epithelial cell adhesion molecule (EpCAM) and the tyrosine-kinase receptor Met (c-Met). The effect of CRT on their expression determines their applicability for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Another prerequisite is that the biomarker's expression on tumor cells is not significantly altered by preoperative radiotherapy since this is often used for MFS. For a variety of tumor types there are established suitable targets for molecular imaging, but for MFS specific immunohistochemical expression profiles have not yet been described [17][18][19][20] .…”
mentioning
confidence: 99%
“…Another prerequisite is that the biomarker's expression on tumor cells is not significantly altered by preoperative radiotherapy since this is often used for MFS. For a variety of tumor types there are established suitable targets for molecular imaging, but for MFS specific immunohistochemical expression profiles have not yet been described [17][18][19][20] .…”
mentioning
confidence: 99%
“…Previous research has shown that CEA and EpCAM expression is upregulated in rectal cancer cells compared with adjacent pre-existent rectal mucosa [ 20 , 34 ]. A previous study by our group has demonstrated that CEA and EpCAM are still overexpressed in patients with a partial or no response after neoadjuvant therapy [ 20 , 34 , 35 ]. In that study, CEA and EpCAM expression after neoadjuvant therapy was high (TIS > 6) in respectively 93% and 100% of the partial- and nonresponders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by our group has demonstrated that CEA and EpCAM are still overexpressed in patients with a partial or no response after neoadjuvant therapy [ 20 , 34 , 35 ]. In that study, CEA and EpCAM expression after neoadjuvant therapy was high (TIS > 6) in respectively 93% and 100% of the partial- and nonresponders [ 35 ]. The current study demonstrates that CEA and EpCAM have an absent or low expression (TIS < 6) in the tumor bed of nearly all patients with a pCR after neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a good level of contrast between healthy and cancer tissue and high antigenic density makes CEA an excellent candidate for fluorescent‐guided surgery in CRC. Furthermore, CEA expression does not seem to alter after neoadjuvant therapy …”
Section: Cea and Crcmentioning
confidence: 98%